The role of humor in social, psychological, and physical well-being - Oliveira, R.; Arriaga, P.; Barreiros, J. (Humor - International Journal of Humor Research, 2023)
Humor is a pervasive part of our daily lives that has several important social functions. Although past literature has suggested the existence of a link between certain components of humor and well-being, the extent and specific characteristics of this link are still unclear. To shed light on this issue, we conducted a scoping review of the literature through which we identified 128 publications examining the association between humor components (i.e., styles of humor, coping humor, sense of humor, comic styles, and laughter) and psychological, physical, social, and general well-being. Overall, findings support a clear positive relation between all components of humor and psychological well-being, and a less pronounced positive association between humor and physical, social, and general well-being.